Survival effect of palliative radiotherapy in patients with metastatic castration-resistant prostate cancer developing oligo-progression under antiandrogen treatment - Göktaş Aydın, Sabin; Kutlu, Yasin; Muğlu, Harun; Açıkgöz, Özgür; Aydın, Ahmet; Bilici, Ahmet; Ölmez, Ömer Fatih; Ünal, Dilek; Karcı, Ebru; Yıldız, Özcan (Istanbul University, 2023)
Objective: Androgen pathway inhibitors have a significant impact on the treatment of prostate cancer. The treatment approach is controversial in patients who develop oligo-pro-gression under anti-androgen therapy. This study aimed to in-vestigate the effects of metastasis-directed stereotactic body radiotherapy (SBRT) on survival in the first-line setting of patients with metastatic castration-resistant prostate cancer who contin-ued the antiandrogen therapy after oligo-progression. Materials and Methods: Fifty-seven metastatic castration-re-sistant (serum testosterone <50 ng/dl) prostate cancer patients treated with abiraterone or enzalutamide in the first-line setting were analysed retrospectively. Thirty-nine of the patients with the oligo-progressive disease, which was defined as <= 3 lesions on imaging, received SBRT by continuing the same antiandro-gen therapy. Results: The median age was 70 (range 40-85). In the castra-tion-sensitive setting, 27 (47.4%) patients received docetaxel. The oligo-progressive metastatic sites were as follows: bone in 21 (52.3%), lymph node in 6 (15.3%) and visceral metastasis in 12 (30.9%) patients. Abiraterone and enzalutamide were preferred in 47.4% and 52.6% of patients, respectively. The 12-month pro-gression-free survival (PFS) was 79.0% and 88.9% in patients who received or did not receive SBRT (p<0.001). SBRT-related grade 1-2 toxicity was observed in 35 (61.4%) patients. SBRT was also an independent risk factor for PFS (p=0.007, HR:15.7; 95% CI 2.05-118.7). The presence of visceral metastases, isolated bone metastases, the choice of anti-androgen therapy, and Eastern Cooperative Oncology Group Scale Performance Status (ECOG PS) were not significantly associated with PFS. SBRT had no im-pact on overall survival. Conclusion: Patients treated with metastasis-directed SBRT without changing treatment in the oligo-progression setting had worse survival outcomes. Thus, metastasis-directed SBRT with continuation of the same antiandrogen therapy should be prior-itised only in selected cases.

Amaç: Androjen yolağı inhibitörleri prostat kanserinin tedavisinde önemli etkiye sahiptir. Anti-androjen tedavisi altında oligo-progresyon gelişen hastalarda tedavi yaklaşımı tartışmalıdır. Bu çalışma, metastaza yönelik stereotaktik vücut radyoterapisinin (SBRT) oligo-ilerlemeden sonra antiandrojen tedavisine devam eden metastatik kastrasyona dirençli prostat kanserli hastalarda birinci basamakta sağkalım üzerindeki etkilerini araştırmayı amaçladı. Gereç ve yöntem: Birinci basamakta abirateron veya enzalutamid ile tedavi edilen 57 metastatik kastrasyon dirençli (serum testosteron <50 ng/dl) prostat kanseri hastası retrospektif olarak analiz edildi. Görüntülemede ?3 lezyon olarak tanımlanan oligo-progresif hastalığı olan 39 hasta aynı antiandrojen tedavisine devam edilerek SBRT aldı. Bulgular: Medyan yaş 70 (dağılım 40-85) idi. Kastrasyona duyarlı ortamda, hastaların 27’si (%47,4) dosetaksel almıştır. Oligo-progresif metastatik bölgeler 21 (%52,3) hastada kemik, 6 (%15,3) hastada lenf nodu ve 12 (%30,9) hastada visseral metastaz olarak saptandı. Abirateron ve enzalutamid sırasıyla %47,4, %52,6hastada tercih edildi. SBRT alan ve almayan hastalarda 12 aylık progresyonsuz sağkalım (PFS) %79,0 ve %88,9 idi (p<0,001). Otuz beş (%61,4) hastada SBRT ile ilişkili derece 1-2 toksisite gözlendi. SBRT ayrıca PFS için bağımsız bir risk faktörüydü (p=0,007, HR:15,7; %95 GA 2,05-118,7). Visseral metastazlar, izole kemik metastazları, anti-androjen tedavi seçimi ve Eastern Cooperative Oncology Group (ECOG) performans skalası varlığı, PFS ile istatistiksel olarak anlamlı değildi. SBRT’nin genel sağkalım üzerinde hiçbir etkisi olmamıştır. Sonuç: Oligo-progresyon durumunda tedaviyi değiştirmeden metastaza yönelik SBRT ile tedavi edilen hastalarda sağkalım sonuçları daha kötüydü. Bu nedenle, aynı antiandrojen tedavisine devam edilerek metastaza yönelik SBRT’ye sadece seçilmiş vakalarda öncelik verilmelidir.
Antiandrojen tedavisi altında oligo-progresyon gelişen metastatik kastrasyona dirençli prostat kanserli hastalarda metastaza yönelik vücut radyoterapisinin sağkalım etkisi
Keywords: Stereotactic Body Radiotherapy; Abiraterone; Enzalutamide; Castration-Resistant Prostate Cancer; Stereotaktik Vücut Radyoterapisi; Abiraterone; Enzalutamide; Kastrasyona Dirençli Prostat Kanseri